Database modelling in Cartography for the “Atlas of Election” - Dobesova, Zdena (Geodesy and Cartography, 2012)
Today maps are prepared in Geographic Information Systems (GIS software) and based on data stored in a database. In the stage of the conceptual database design, the graphic editor of a database model is recommended. The structure of data is often under the influence of the cartographic requests. For example, new data may be added only for visualization purposes. All database structures for a base data and a cartographical data can be defined in a conceptual database model before creation of a physical database model. Database modelling is demonstrated in ArcGIS Diagrammer software in this article. Design of a cartographic database model for the book “Atlas of Election to the Olomouc Region Council” is used as an example. Moreover, steps of a model creation, detail structure and relationships in the model are also mentioned. The cartographical database model of the “Atlas of Election” illustrates cartographical influence to the database structure.